Determinants of maternal near-miss event’s among pregnant women attending tertiary care hospital: A case–control study - Rutuja Patond; Ramesh Pawar; Sanjeev Chaudhary; Mahesh Puri; Vijay Balkar (Asian Journal of Medical Sciences, 2023)
Background: Women who have survived complications during pregnancy and childbirth have been studied as surrogates of maternal deaths and have been termed as maternal near-miss. Study of such cases is considered a less threatening approach to improve maternal health care by the service providers. With this tool, we will be able to identify the delays. As near-miss occurs much more frequently than maternal deaths, a more reliable quantitative analysis can provide a comprehensive profile of the health system functioning. Near-misses are relatively simpler to analyze and easier to resolve. This knowledge will help in identifying the contributory factors of maternal deaths so that actions can be taken at community and health systems level.